2019
DOI: 10.12659/msm.917142
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis Identifies Protein Tyrosine Kinase 7 (PTK7) as a Potential Prognostic and Therapeutic Biomarker in Stages I to IV Hepatocellular Carcinoma

Abstract: Background: Worldwide, hepatocellular carcinoma (HCC) accounts for 80-90% of all cases of primary liver cancer, and is one of the ten most common malignancies. This study used bioinformatics analysis to identify genes associated with patient outcome in stages I-IV HCC and the gene pathways that distinguished between normal liver and liver cells and HCC and human HCC cell lines. Material/Methods: Target genes were defined as those that had marketed drugs or drugs under development targeting a specific gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Oncogenic functions of PTK7 have been documented in several hematological and solid tumors (10,11). Recent studies showed that PTK7 is overexpressed in triplenegative breast cancer (TNBC), non-small-cell lung cancer (NSCLC), ovarian cancer (OVCA), cervical cancer, esophageal squamous cell carcinoma (ESCC), and hepatocellular carcinoma (HCC) and enriched in tumor-initiating cells (TICs) from TNBC, OVCA, and NSCLC patient-derived xenografts (PDXs), and its overexpression is associated with poor survival in NSCLC, cervical cancer, ESCC, and HCC (12,(17)(18)(19)(20)(21)(22). Bie J et al found that PTK7 was dramatically upregulated in the ESCC tissues and cancer stem cell (CSC)-like cells and its knockdown reduced sphere formation, promoted apoptosis, and suppressed invasive behavior of tumor cells (17).…”
Section: Chimeric Antigen Receptor (Car)-modified T-cell (Car T-cell)mentioning
confidence: 99%
“…Oncogenic functions of PTK7 have been documented in several hematological and solid tumors (10,11). Recent studies showed that PTK7 is overexpressed in triplenegative breast cancer (TNBC), non-small-cell lung cancer (NSCLC), ovarian cancer (OVCA), cervical cancer, esophageal squamous cell carcinoma (ESCC), and hepatocellular carcinoma (HCC) and enriched in tumor-initiating cells (TICs) from TNBC, OVCA, and NSCLC patient-derived xenografts (PDXs), and its overexpression is associated with poor survival in NSCLC, cervical cancer, ESCC, and HCC (12,(17)(18)(19)(20)(21)(22). Bie J et al found that PTK7 was dramatically upregulated in the ESCC tissues and cancer stem cell (CSC)-like cells and its knockdown reduced sphere formation, promoted apoptosis, and suppressed invasive behavior of tumor cells (17).…”
Section: Chimeric Antigen Receptor (Car)-modified T-cell (Car T-cell)mentioning
confidence: 99%
“…The expression and function of PTK7 have been investigated in several human cancers, although controversial results have been obtained (18)(19)(20)(21)(22)(23)(24). PTK7 is highly expressed and plays an oncogenic role in lung adenocarcinoma (18).…”
Section: Introductionmentioning
confidence: 99%
“…PTK7 is overexpressed and contributes to thyroid (19) and cervical (22) cancer progression. A bioinformatics analysis reported that PTK7 is highly expressed in stage I-IV hepatocellular carcinoma (HCC) and considered as an independent prognostic marker for reduced overall survival (21). Another investigation of PTK7 expression in 79 consecutive invasive breast cancer tissues by immunohistochemistry found that PTK7 expression level negatively associates with tumor grade and lymph node metastasis (23).…”
Section: Introductionmentioning
confidence: 99%
“…especially in China. Moreover, less than 20% of patients with this malignant tumor are still alive more than half a year after diagnosis [1][2][3][4]. For many years, efforts towards the treatment of liver cancer were focused on the liver cancer cells themselves.…”
mentioning
confidence: 99%